1991
DOI: 10.2514/3.46010
|View full text |Cite
|
Sign up to set email alerts
|

Tip vortex/airfoil interaction for a low Reynolds number canard/wingconfiguration

Abstract: The effects of the vortical wake shed by a finite span canard on a low Reynolds number airfoil were examined. Aerodynamic performance was evaluated through direct measurements of lift, drag, and 1/4-chord pitching moment. Spanwise static pressure and surface film visualization data were also acquired. A reduction in the downstream airfoil drag coefficient and an increase in its lift/drag were noted in the presence of the canard for a wide range of configurations. Static pressure and surface visualization data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Historically, biplane wings offered increased planform area and increased structural rigidity through inter-wing bracing. With the development of monoplane aircraft, biplane aircraft were largely relegated to sport aviation [7,8]. However, previous studies have demonstrated that two wing configurations can delay stall at low Reynolds numbers [1,9].…”
Section: Stall Delay Of Two-wing Configurations With Decalage At Low mentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, biplane wings offered increased planform area and increased structural rigidity through inter-wing bracing. With the development of monoplane aircraft, biplane aircraft were largely relegated to sport aviation [7,8]. However, previous studies have demonstrated that two wing configurations can delay stall at low Reynolds numbers [1,9].…”
Section: Stall Delay Of Two-wing Configurations With Decalage At Low mentioning
confidence: 99%
“…Several studies have considered the effects of decalage (differing wing angle: δ = α1 -α2) [7,10,11]. However, many of these studies only consider the effects at large gaps or stagger (typically fixed at or above one chord) missing the region of greatest potential improvement [1].…”
Section: Stall Delay Of Two-wing Configurations With Decalage At Low mentioning
confidence: 99%
See 1 more Smart Citation
“…The normal BVI is, however, of particular significance when the main rotor tip vortices pass through and normal to the tail rotor disk -a situation that exists under most flight conditions, which gives rise to an increase in tail rotor noise due to the main rotor/tail rotor vortex interaction see for instance, [7][8] . Normal BVI is also observed when the vortical wake shed by a finite span canard impinges on a wing 9 . The majority of the research, however, has been performed for the case of main rotor BVI where the vortex interacts with another main rotor blade 11 .…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, they have explored wings encountering wakes characterised by various vortical structures that differ in strength, orientation (both parallel and perpendicular), wavelength, frequency and length scales. These studies have analysed how such wake disturbances alter the aerodynamic response and performance of the downstream wing [4,[10][11][12][13][14][15]. However, there has been more limited investigation into the upstream effects of a rear wing on the aerodynamics of a forward wing and the wake interactions between them.…”
Section: Introductionmentioning
confidence: 99%